2005
DOI: 10.1523/jneurosci.0635-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

MONaKA, a Novel Modulator of the Plasma Membrane Na,K-ATPase

Abstract: We have cloned and characterized mouse and human variants of MONaKA, a novel protein that interacts with and modulates the plasma membrane Na,K-ATPase. MONaKA was cloned based on its sequence homology to the Drosophila Slowpoke channel-binding protein dSlob, but mouse and human MONaKA do not bind to mammalian Slowpoke channels. At least two splice variants of MONaKA exist; the splicing is conserved perfectly between mouse and human, suggesting that it serves some important function. Both splice variants of MON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…PXK encodes a multimodular protein composed of a phox homology domain, a protein kinase-like domain, and a WiskottAldrich syndrome protein homology 2 domain. The gene product of PXK regulates the activity of Na-ATPase and K-ATPase ion transport, and is expressed in the kidney (57,58). Recent data suggest that PXK has a critical role in trafficking of the EGF receptor through modulation of ligandinduced ubiquitination of the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…PXK encodes a multimodular protein composed of a phox homology domain, a protein kinase-like domain, and a WiskottAldrich syndrome protein homology 2 domain. The gene product of PXK regulates the activity of Na-ATPase and K-ATPase ion transport, and is expressed in the kidney (57,58). Recent data suggest that PXK has a critical role in trafficking of the EGF receptor through modulation of ligandinduced ubiquitination of the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Zou et al reported that there were five splice variants of the human PXK gene with different subcellular localization (75), and Mao et al showed that PXK, designated MONaKA (modulator of Na,K-ATPase), modulated the activity of the Na,K- ATPase, as assessed by catalytic activity and functional ion transport activity, by directly interacting with the ␤-subunit (45). The ubiquitous tissue distribution of PXK, analyzed by Northern blotting and Western blotting in this study, correlated with the results obtained by reverse transcription-PCR analyses in those reports.…”
Section: Discussionmentioning
confidence: 99%
“…The following primers were used for PCR: F1, 5Ј-GCAAGGTGCTGCT GGACGACAC-3Ј; F2, 5Ј-AGCCAAAGTGGGAGGTGGTGGAAC-3Ј; R1, 5Ј-ACTTGTCTGGGCCAAGGTCAGC-3Ј; and R2, TCAAGGTCCAGCAGC-CGGCAAG-3Ј. PCR was performed with F1/R1, F1/R2, and F2/R2 primer sets to detect several splice variants of PXK (45), and the reaction with each combination of primers gave a single band.…”
Section: Methodsmentioning
confidence: 99%
“…The 3p14 region with suggestive evidence for linkage harbors candidate genes such as: FEZF2 (3p14.2), which regulates the specification of corticospinal motor neurons and sub-cerebral projection neurons [Molyneaux et al, 2007] may also be involved in innate immunity; CADPS (3p14.2), expressed in brain, neural and endocrine-specific tissue, which encodes a calcium-binding membrane protein essential for exocytosis of vesicles filled with neurotransmitters and neuropeptides [Binda et al, 2005]; SYNPR (3p14.2), isolated from brain, which encodes a membrane protein of synaptic vesicles and up-regulation was noted upon peripheral nerve injury [Sun et al, 2006]; ABHD6 (3p14.3), which codes a brain enzyme that has been implicated in endocannabinoid signaling [Blankman et al, 2007]; PXK (3p14.3), whose functions include cell communication and regulation of synaptic transmission [Mao et al, 2005;Zhang et al, 2009]; KCTD6 (3p14.3), which involved in voltage-gated potassium channel activity; and ACOX2 (3p14.3), which is implicated in neurodevelopmental delay and brain dysfunction [Wanders and Waterham, 2006].…”
Section: Discussionmentioning
confidence: 99%